PROBLEMATIKA PENGEMBANGAN PPRA MELALUI PROGRAM TAHFIDZ DI MADRASAH IBTIDAIYAH - Rodliyatin Ni’am (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Moral degradation is rife today, particularly among teenagers, and one example is a decline in students' manners. To address this challenge, MI Miftahul Huda has implemented an integrated PPRA program with education that instills religious values, thereby enhancing students' faith, piety, morals, and religious character. The purpose of this study is to identify problems related to the formation of PPRA through the tahfidz program. The research method uses a phenomenological approach as a qualitative research method. Data collection was obtained from primary and secondary sources. Primary data were obtained from observations and interviews, while secondary data were obtained from other documents supporting this research. The data obtained was then evaluated using source triangulation techniques, followed by analysis. The research findings indicate that the tahfidz program was implemented using the muroja'ah method, beginning with communal prayer, reciting the sholawat nariyah, ayat kursi, Asmaul Husna, short surahs, and daily prayers. Problems that occur from the implementation of this program can be caused by internal and external factors, such as limited competent human resources, differences in student ability levels, limited time, schedules, parental support, environment, motivation, student interests, and different student abilities, as well as some students still being left behind or not yet memorized. To overcome this problem, MI Miftahul Huda routinely conducts program evaluations and monitoring on a regular basis to address problems that occur in the implementation of the program.